Simplex didactics: promoting transversal learning through the training of perspective taking - Stefano Di Tore; Paola Aiello; Maurizio Sibilio; Alain Berthoz (Je-LKS: Journal of E-Learning and Knowledge Society, 2020)
Several studies have focused on Visual Perspective Taking (from here on out “PT”). PT refer to the capacity to elaborate space from different perspectives. Research results led to the hypothesis that such an ability constitutes a milestone in the development of an individual’s social skills, more specifically empathy, whose full development is at the basis of numerous school-related competencies. Even the national educational system seems to recognise the central role of the development of such skill in students’ learning. To date, there is a lack of studies and teaching methods specifically designed to favour an adequate development of PT. The objective of this paper is to present the results of the validation of an edugame specifically designed to measure and promote the PT skill development.